PENINGKATAN PEMAHAMAN MASYARATAKAT TENTANG PENYAKIT DIABETES MELLITUS (KENCING MANIS) DAN PENGOBATANNYA PADA MASYARAKAT RT 01 RW 01 DAN RT 07 RW 02 KELURAHAN SUKAJAYA PALEMBANG - Hutabarat, Mustika Sari; Hotman Sinaga (Jurnal Pengabdian Ilmu Kesehatan, 2022)
Diabetes mellitus (DM) is a metabolic disease characterized by increased blood glucose levels. ). DM is known as the silent killer because it is often not realized by the sufferer and when it is known that complications have occurred, therefore it is necessary to take preventive measures that can be done by attending seminars or counseling related to health and conducting regular health checks. The implementation of counseling about DM disease to increase public understanding so that many people begin to regulate a healthy lifestyle and for people who have a history of DM disease can reduce the occurrence of complications. The target of the counseling is the community of RT 01 and RT 02 in Sukajaya Village, Palembang. From the results of this activity as many as 116 participants who took part in counseling and blood sugar checks, from the results of blood sugar examinations, 10 people (8.6%) had sugar levels <150 mg/dL and received medication while 106 people (91.4 %) had normal blood sugar levels.